Comparison of Lagrangian Bounds for One Class of Generalized Assignment Problems - Litvinchev, I.; Rangel, S. [UNESP] (Maik Nauka/interperiodica/springer, 2008)
Classical and modified Lagrangian bounds for the optimal value of optimization problems with a double decomposable structure are examined. For the class of generalized assignment problems, this property of constraints is used to design a Benders algorithm for solving the modified dual problem. Numerical results are presented that compare the quality of classical and modified bounds.
Keywords: Lagrangian bounds in optimization problems; improvement of Lagrangian bounds; generalized assignment problem